Relação da imunoexpressão da BMP-2, BMPR-IA e BMPR-II com o perfil clínico-patológico em carcinoma epidermóide de lábio inferior - Carvalho, Cyntia Helena Pereira de (2010)
Currently, bone morphogenetic proteins (BMPs) have effective participation in the growth of malignancies. Knowing that there are few studies involving BMPs and oral squamous cell carcinoma, this work constitutes an immunohistochemical study of BMP-2, BMPR IA and BMPR II in squamous cell carcinomas (SCC) of the lower lip relating to the clinical and pathological aspects of this lesion. The sample consisted of 40 cases of SCC of the lower lip, being 20 cases of SCC of the lower lip with regional metastasis and 20 cases without metastasis. We evaluated the intensity of expression (score 1 to mark absent / weak, score 2 for high ) and was found the percentage of labeled cells, where the score was 1 cases with 0 to 50% of positive cells, score 2 with 51 to 75% of positive cells, and score 3 more than 75% of positive cells. The sample comprised 72.5% of men with a mean age of 65.8 years, there was a predominance of stage II and 52.5% of the carcinomas were classified as low grade, being carcinoma with metastasis presenting most cases (70%) as carcinomas of high malignancy grade (p = 0.004). The largest number of cases of SCC of the lower lip that were in stages I / II (61, 9%) were classified as carcinomas of low grade malignancy and carcinomas in stages III / IV were classified as high-grade tumors (p = 0, 024). The BMP-2 showed strong intensity of immunostaining in 82.5%, BMPR-IA showed 55% of cases with an intensity of immunostaining absent / weak and BMPR-II showed 85% of cases with an intensity of immunostaining absent / weak. Only the protein BMPR-IA were significantly associated with all clinic-pathological parameters studied, metastasis (p <0.001), TNM (p <0.001) and histological grade of malignancy with (p = 0.028). The percentage of positive cells, all markers showed the highest number of cases with more than 75% of positive cells (score 3) and only BMPR-II showed statistical difference when related to the presence and absence of metastasis (p = 0.049 ). We conclude that there is disturbance in the BMP signaling pathway in EC-mediated lower lip and that high expression of BMP-2 associated with the expression of BMPR-IA and BMPR-II are associated with metastasis in carcinoma